An Uninvestigated Risk Factor for Contrast-Induced Nephropathy in Chronic Kidney Disease: Proteinuria. (February 2013) - Piskinpasa, Serhan; Altun, Bulent; Akoglu, Hadim; Yildirim, Tolga; Agbaht, Kemal; Yilmaz, Rahmi; Peynircioglu, Bora; Cil, Barbaros; Aytemir, Kudret; Turgan, Cetin
<x xml:space="preserve">Abstract</x> Background: Contrast-induced nephropathy (CIN) is one of the most frequent causes of acute renal failure in hospitalized patients with the incremental use of contrast media. We aimed to investigate whether proteinuria may act as a risk factor for CIN in patients with chronic kidney disease. Methods: Seventy hospitalized patients (37 men, 33 women) with chronic kidney disease, proteinuria, and/or estimated glomerular filtration rate (eGFR) of <60 mL/min/1.73 m2, who were exposed to contrast media were investigated prospectively. Thirty patients were diabetic. All patients received prophylaxis against CIN with acetylcysteine and 0.9% intravenous saline. CIN is defined as either a 25% higher increase in serum creatinine (sCr) from the baseline levels or a 0.5 mg/dL increase in sCr at 72 h after contrast media exposure. Results: CIN was detected in 26 (37.1%) patients. Advanced age, diabetes, heart failure, anemia, baseline sCr of >1.5 mg/dL, baseline eGFR of <60 mL/min/1.73 m2, proteinuria of ≥1 g/day, hypoalbuminemia, and the volume of contrast media of ≥100 mL correlated significantly with CIN. The frequency of CIN was significantly higher in patients with proteinuria of ≥1 g/day compared to patients with proteinuria of <1 g/day (p = 0.009). Conclusion: Proteinuria may be a new risk factor for the development of CIN in patients with chronic kidney disease.